Industrial Sociology - Lakewood, Obrian S. (Dublin Oryson Press, 2024)
Industrial Sociology is a branch of Sociology that looks at the impact of labour and industry on society.as well as the ways in which society impacts industrial forces. The prospective used within this discipline very over time, and given the practical value of undersetting this relationship, this type of study has often been very well supported. there are many topics within this field that merit individual investigation, including technologies used, work relations and even subjects as broad as globalisation.
Keywords: Economy Sector; Labour Economics; Globalization and Trade Liberalization; Economic Work Relation